Accelerating space life sciences via astronaut omics collection and integrated analyses - Cope, Henry (2024)
There are ambitious plans for human spaceflight on the horizon, including an increasingly diverse spacefaring population associated with a variety of commercial ventures, a return to the Moon, and deep-space voyages with the eventual goal of colonising Mars. Past missions - including continuous occupation of the International Space Station since the turn of the millennium - have highlighted stressors associated with spaceflight, such as altered gravity (including “microgravity”, which refers to the near-weightlessness experienced due to low gravitational forces, such as during continuous freefall within orbiting spacecraft), cosmic radiation, isolation, and confinement within a closed spacecraft environment. These spaceflight stressors incite a distinct set of molecular effects and associated physiological and psychological changes that elevate the risk of certain health issues in humans and other Earth-based life. Health risks include loss of performance due to degradation of bone and muscle, skin rashes, vision problems, and cognitive and psychiatric disorders. These changes occur dynamically throughout the course of a mission and manifest variably based on differences between individuals and environmental parameters. The changing landscape of human spaceflight necessitates investigation into the precise mechanisms behind these detrimental biological changes, so that the interplay of risk factors can be comprehensively understood and countermeasures can be developed to increase safety and the likelihood of success across missions.